Review of Research on Middle School English Teaching Strategies based on Project - Based Learning - Xia, Conghui (International Journal of Social Sciences and Public Administration, 2025)
In the context of continuous educational innovation, project - based learning, as an innovative teaching model, has received extensive attention in the field of middle school English teaching. With elements such as authentic tasks, driving questions, and an emphasis on students’ dominant position, it integrates deeply with middle school English teaching, significantly enhancing students’ comprehensive language application ability, thinking quality, and cultural awareness. Teachers can promote in - depth learning effectively by identifying projects that fit the unit theme and students’ interests, creating real - life situations, and guiding students to conduct cooperative inquiries. However, in practice, project - based learning still faces many challenges, such as insufficient teacher guidance capabilities, a lack of teaching resources, and an imperfect evaluation system. Future research should focus on developing targeted teacher training programs, exploring efficient resource integration strategies, and constructing a scientific and comprehensive evaluation system to promote the wide application and optimization of project - based learning in middle school English teaching, facilitate the cultivation of core competencies in the English subject, improve the quality of middle school English teaching, and achieve the educational goals of the English subject.